2014
DOI: 10.9790/0853-13567175
|View full text |Cite
|
Sign up to set email alerts
|

A study of disease pattern in patients presenting in the emergency department of a tertiary hospital catering to industrial workers

Abstract: Emergency department (in a health care facility) is a section of an institution that is staffed and equipped to provide rapid and varied emergency care, especially for those who are stricken with sudden and acute illness or who are the victims of severe trauma. This study analyzed the disease pattern of patients presenting to the emergency department of a tertiary care insurance based hospital in Delhi. The results showed maximum patients attended were under the Medicine and Surgery discipline. A large proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Trauma related major neurosurgical (often head injuries) and orthopedic (such as long bone fracture) cases constitute 11.4%. The finding is almost similar to a tertiary hospital in Delhi where major orthopedic cases alone constitute 11.64% [8].…”
Section: Discussionsupporting
confidence: 78%
“…Trauma related major neurosurgical (often head injuries) and orthopedic (such as long bone fracture) cases constitute 11.4%. The finding is almost similar to a tertiary hospital in Delhi where major orthopedic cases alone constitute 11.64% [8].…”
Section: Discussionsupporting
confidence: 78%
“…In this study majority of the service receivers 101(57.7%) were transferred to IPD and 23(23.23%) were transferred to the Medicine of IPD from ED. In a study by Jitesh Dhingra et al, found that, Most of the Patients 56.08% were transferred to the Medicine of IPD from ED [11]. Opinion regarding overall management, 45.7% was satisfied.…”
Section: Resultsmentioning
confidence: 96%